Throughput Analysis for Wireless Step Network - Zaidi, Taskeen; Dwivedi, Nitya Nand (International Journal of Computer Sciences and Engineering, 2019)
TXOP is the transmission opportunity scheme given by IEEE 802.11e to enhance the Quality of Service(QoS).This paper observed the TXOP service differentiation for the devices/nodes connected in step network and metrics like throughput is derived. In the current work the simulation is carried out using NS3 and performance of four networks with QoS were estimated by enabling and disabling TXOP and it was observed throughput rate will be increased when TXOP is enabled and decreased when TXOP is disabled.